EFFECT OF THERAPEUTIC EXERCISE IN IMPROVING THE QUALITY OF LIFE IN ELDERLY WOMEN - báñez-Gómez, M J (Cuestiones de Fisioterapia, 2012)
Aims: to verify the efficiency of the physical therapeutic activity for the improvement of the quality of life in a group of elderly women, as well as the relation of this improvement with different variables. Material and method:Randomized control trial. Seventeen women of a center for elderly in Jaen that they meet the criteria of selection (over 60-year-old, independent women in the activities of the daily life, cognitive normal level, to complete period of tre-atment and foreseen evaluations, between others, as well as signature of informed assent). They took part in a pro-gram of physical activity in field and nine took part, additional, in aquatic way. His quality of life was evaluated by the Questionnaire of health SF-36, before and after the intervention. Variables were related as the age, and. civilian, and the IMC. Results: the improvement in the quality of life by means of the Questionnaire of Health SF-36 was-404.41 points (p <0.0001). With regard to the age 71.88 (DT 5.30) the improvement 404.41 (DT 159.19) was indeed sta-tistically significant. (p < 0.0001). As for the comparison of the improvement and the IMC 30.52 (DT 4.02), it was statistically significant (p < 0.0001). Whereas the hydrotherapy (p = 0.0679) and the marital status (p = 0.3438) did not influence the improvement. The force of association between the initial and final punctuation is good enough r (X,Y) = 0.723. 52.32 % of the final punctuation owes to the effect of the initial punctuation (R2 = 0.523223). Conclusions: therapeutical physical activity improves the quality of life of elderly women. The age and the IMC influenced in a significant way but not the marital status, or the addition of hydrotherapy an hour a week. The field therapy (3 sessions per week) consisting in a coordinated dance including warm up, aerobic and stretching's exercises improves the physical, mental and social function and, with it, the health in this vital cycle.